2021
DOI: 10.3389/fcimb.2021.670424
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota of Critically Ill Patients With COVID-19

Abstract: The SARS-CoV-2-associated COVID-19 pandemic has shaken the global healthcare system. Although the best-known symptoms are dry cough and pneumonia, viral RNA has been detected in the stool and about half of COVID-19 patients exhibit gastrointestinal upset. In this scenario, special attention is being paid to the possible role of the gut microbiota (GM). Fecal samples from 69 COVID-19 patients from three different hospitals of Bologna (Italy) were analyzed by 16S rRNA gene-based sequencing. The GM profile was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 41 publications
10
95
0
1
Order By: Relevance
“…We identified multiple species with highly similar genomes from those permissive nrMAGs ( Fig.5b ), including Enterocloster bolteae (3 nrMAGs), Anaeroglobus micronuciformis, Hungatella effluvii (3 nrMAGs), and Enterococcus B faecium . Consistent with previous reports that the gut microbiome of COVID-19 patients showed significant higher abundance of Enterococcus faecium compared to health controls 46 . Among the 63 protective nrMAGs, the dominant species were Blautia A obeum (13 nrMAGs), Bariatricus comes (9 nrMAGs), Faecalibacterium prausnitzii D (6 nrMAGs), Blautia A wexlerae (6 nrMAGs), Faecalibacterium sp900539945 (4 nrMAGs), Dorea longicatena B (3 nrMAGs), Blautia A sp003480185 (3 nrMAGs), Blautia A sp003471165 (3 nrMAGs), Dorea formicigenerans (2 nrMAGs), Fusicatenibacter saccharivorans (2 nrMAGs), and GCA-900066135 sp900543575 (2 nrMAGs).…”
Section: Resultssupporting
confidence: 92%
“…We identified multiple species with highly similar genomes from those permissive nrMAGs ( Fig.5b ), including Enterocloster bolteae (3 nrMAGs), Anaeroglobus micronuciformis, Hungatella effluvii (3 nrMAGs), and Enterococcus B faecium . Consistent with previous reports that the gut microbiome of COVID-19 patients showed significant higher abundance of Enterococcus faecium compared to health controls 46 . Among the 63 protective nrMAGs, the dominant species were Blautia A obeum (13 nrMAGs), Bariatricus comes (9 nrMAGs), Faecalibacterium prausnitzii D (6 nrMAGs), Blautia A wexlerae (6 nrMAGs), Faecalibacterium sp900539945 (4 nrMAGs), Dorea longicatena B (3 nrMAGs), Blautia A sp003480185 (3 nrMAGs), Blautia A sp003471165 (3 nrMAGs), Dorea formicigenerans (2 nrMAGs), Fusicatenibacter saccharivorans (2 nrMAGs), and GCA-900066135 sp900543575 (2 nrMAGs).…”
Section: Resultssupporting
confidence: 92%
“…We found that the dysbiosis of gut microbiota may be a determinant factor in the clinical severity of COVID-19. Increase of the dominant Enterococcus and reduction of Ruminococcaceae and Lachnospiraceae are reported in severe cases of COVID-19 who were admitted to the medical intensive unit (MICU) (Gaibani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae, which is known as SCFA-producing bacteria, decreases in patients with COVID-19 (d'Ettorre et al, 2020;Gu et al, 2020b;Zuo et al, 2020a;Cao et al, 2021;Gaibani et al, 2021;Gautier et al, 2021;Zuo et al, 2021a). It may be attributed common use of azithromycin and other antibiotics in the management of COVID-19 (Segal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with non-infected individuals, gut dysbiosis in patients with COVID-19 is marked by the depletion of C. leptum (cluster IV) group, F. prausnitzii , and E. rectale species, Ruminococcaceae , and Lachnospiraceae families, in conjunction with the overgrowth of Enterococcus genus, Veillonellaceae , and Enterobacteriaceae families ( Tang et al, 2020 ; Tao et al, 2020 ; Zuo et al, 2020 , 2021 ; Gaibani et al, 2021 ; He et al, 2021 ; Wu et al, 2021 ; Yeoh et al, 2021 ). The abundance of Coprobacillus , C. ramosum , C. hathewayi ( Zuo et al, 2020 ), and Enterococcus ( Gaibani et al, 2021 ) was found positively correlated with COVID-19 severity; conversely, an inverse correlation was observed between the disease severity and the abundance of C. leptum (cluster IV) group, Lactobacillus , Bifidobacterium , C. butyricum ( Tang et al, 2020 ), Bilophila , Citrobacter ( Tao et al, 2020 ), Bacteroides ( Gaibani et al, 2021 ), F. prausnitzii , E. rectale ( Tang et al, 2020 ; Yeoh et al, 2021 ), B. bifidum , and B. adolescentis ( Yeoh et al, 2021 ). In addition, the abundance of some microbial taxa, including Erysipelotrichaceae bacterium 2_2_44A ( Zuo et al, 2020 ), P. copri , E. dolichum ( Wu et al, 2021 ), C. aerofaciens , C. tanakaei , S. infantis ( Zuo et al, 2021 ) positively correlates with the fecal SARS-CoV-2 load.…”
Section: Gut Microbiota In Sars-cov-2 Infectionmentioning
confidence: 99%